ANALISIS NEWMAN PADA SOAL-SOAL AKM MATEMATIKA DI KELAS V SD - Putri Indah Sari; Sukmawarti Sukmawarti (Jurnal Inovasi Penelitian, 2023)
This research aims to determine Newman's analysis of AKM mathematics questions for students in class V elementary school. This research is descriptive research with a qualitative approach. This research was conducted in class V of SDS Al-Washliyah Paya Lombang, Hamlet XII, Tebing Tinggi District, Tebing Tinggi City. The participants in this research were 20 class V teachers and class V students at SDS Al-Washliyah Paya Lombang. The data collection techniques used were observation, interviews and documentation. The stages of data analysis carried out were data reduction, data presentation and drawing conclusions. From the stages of the Newman procedure carried out, the researcher found several questions that were unclear, both in terms of sentence structure and unit designation. Even though it is not often found, of course this can cause students to answer the AKM questions incorrectly in the book. From the results of the analysis, it is known that there are 3 types of student errors in solving AKM mathematics questions, namely errors in understanding the problem (comprehension), errors in processing skills and errors in writing answers (encoding).